Relationship between Risk Behavior for Eating Disorders and Dental Caries and Dental Erosion - Lorenna Mendes Temóteo Brandt; Liege Helena Freitas Fernandes; Amanda Silva Aragão; Yêska Paola Costa Aguiar; Sheyla Márcia Auad; Ricardo Dias de Castro; Sérgio D’Ávila Lins Bezerra Cavalcanti; Alessandro Leite Cavalcanti (The Scientific World Journal)
The aim of this study was to evaluate whether there is an association between risk behavior for eating disorders (EDs) and dental erosion and caries. A controlled cross-sectional study was conducted in Brazil, involving 850 randomly selected female adolescents. After evaluating risk behavior for eating disorders through the Bulimic Investigatory Test of Edinburgh, 12 adolescents were identified with severe risk behavior for EDs and matched to 48 adolescents without such risk. Dental examinations, anthropometric measurements, and eating habits and oral hygiene were performed. Adolescents with high severity eating disorder condition were not more likely to show dental caries (p=0.329; OR = 2.2, 95% CI: 0.35–13.72) or dental erosion (p=0.590; OR = 2.33; 95% CI: 0.56–9.70). Adolescents with high body mass index (BMI) were five times more likely to have high severity eating disorder condition (p=0.031; OR = 5.1; 95% CI: 1.61–23.07). Therefore, high severity risk behavior for EDs was not significantly associated with dental caries and dental erosion. However, high BMI was a risk factor for developing eating disorders and should be an alert for individuals with this condition.